Influence of probe geometry in micro-scale impact testing of nano-multilayered TiAlCrN/NbN coatings deposited on WC-Co. (February 2021) - Beake, B.D.; Bergdoll, L.; Isern, L.; Endrino, J.L.; Fox-Rabinovich, G.S.; Veldhuis, S.C.
Abstract: Hard nano-multilayered TiAlCrN/NbN coatings on cemented carbide have shown promise in dry high speed machining applications involving repetitive contact, such as end milling of hardened H13 steel. In this study the fracture resistance of TiAlCrN/NbN coatings under repetitive dynamic high strain rate loading has been evaluated by the micro-scale impact test method. Although the fatigue mechanisms can vary with the ratio of coating thickness t to the indenter radius R, macro-scale tests of thin coatings using probe radii in the mm range are necessarily at low t / R . Micro-impact tests at higher t / R have been performed with a range of diamond indenter geometries ( R = 8, 20, 100 μm) to investigate the role of varying t / R (0.03–0.375) on the deformation behaviour. With the largest radius probe there was no clear failure for the coatings or substrate under the test conditions. With the 8 and 20 μm radius probes the behaviour of the coatings was strongly load-dependent and they were more susceptible to impact-induced damage than the carbide substrate. As the load increased there was a change from coating to substrate dominated deformation behaviour as the stress field extended further into the substrate. At lower load the dominant fracture behaviour was coating fracture through ring cracking, radial cracking and chipping. At higher load chipping became less prevalent and break-up of the carbide substrate more extensive. Highlights: Applied load and probe sharpness control deformation in micro-impact. Damage can be tailored to affect coating, substrate or interface. Ratio of coating thickness to probe radius influences deformation. High t/R and lower load micro impacts generate damage within the coating. Damage at lower load occurs by a three step process.